Didactic Approaches to the Teaching Pharmacotherapy in Pediatrics - O.P. Pakholchuk (Zaslavsky O.Yu., 2014)
Clinical reasoning formation is impossible without correct organization of the teaching process. Aim of the study was to indicate didactic approaches to teaching pharmacotherapy to students in pediatrics, to define methodological principles of the practical lessons planning. Methods of the study: theoretical analysis of the methodical and medical literature, achieved experience. Results. Analysis enabled to indicate main approaches to the organization of the teaching process following principle from simple to complex. The integration of forms of training and supervision within the faculty and hospital didactic approaches is expected. The need of individualization, the requirements for knowledge of the principles of pharmacoeconomics and evidence-based medicine is considered. Conclusions. An integrated approach, maintaining continuity of didactic teaching approaches will consolidate the knowledge and skills of the student.